2019
DOI: 10.1111/1756-185x.13596
|View full text |Cite
|
Sign up to set email alerts
|

Infection risks of rituximab versus non‐rituximab treatment for rheumatoid arthritis: A systematic review and meta‐analysis

Abstract: Objective: The aim of this study was to assess the differences in infection rates between rituximab (RTX) and non-RTX treatment in patients with rheumatoid arthritis (RA). Methods:A systematic review and meta-analysis was conducted by searching databases of PubMed, MEDLINE, EMBASE, Web of Science and Cochrane Library through to June 2018. We included studies that compared RTX and non-RTX treatment for patients with RA. Outcome measures were overall infections and serious infections between RTX and non-RTX trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 30 publications
1
7
0
1
Order By: Relevance
“…53,54 In our study, we observed a high rate of severe infections (75.7%), mainly of bacterial origin (61.5%). Consistent with reassuring data from the literature, 57,58 this high rate does not seem related to the specific use of RTX but could be explained by the underlying disease or the associated immunosuppression. In multivariable analysis, the rate of infection was associated with low rates of gamma globulins at 3 months, which could be due to nephrotic syndrome 59 or both RTX 60,61 and PP.…”
Section: Ajtsupporting
confidence: 86%
“…53,54 In our study, we observed a high rate of severe infections (75.7%), mainly of bacterial origin (61.5%). Consistent with reassuring data from the literature, 57,58 this high rate does not seem related to the specific use of RTX but could be explained by the underlying disease or the associated immunosuppression. In multivariable analysis, the rate of infection was associated with low rates of gamma globulins at 3 months, which could be due to nephrotic syndrome 59 or both RTX 60,61 and PP.…”
Section: Ajtsupporting
confidence: 86%
“…Pooled analysis of cohort and randomised studies showed no significant differences between rituximab and other treatment groups both in overall infections and in serious infections (4.1% vs 4.6%; OR 1.05; 95% CI 0.84 to 1.31). 24 A Cochrane review of eight trials in rituximab in conjunction with methotrexate for RA compared with methotrexate alone showed no significant difference in the risk of all infections (relative risk [RR] 1.1, 95% CI 0.95 to 1.30) or serious infections (RR 0.68, 95% CI 0.42 to 1.10). 25 One observational study suggested a higher risk of infection with rituximab compared with other biologics, although this has not been found in other observational studies.…”
Section: Cd20 Targeting For B Cell Depletionmentioning
confidence: 99%
“…Rituximab has specific risks based on its mechanism of action; however, it has not shown additional risk of acquiring infection in patients with rheumatoid arthritis 44 or bullous diseases 45 . A low‐dose regimen (500–1000 mg ×2) used in dermatology may result in fewer infections than the standard dose used in haematology (375 mg/m 2 weekly ×4) 46 .…”
Section: Immune Pathways Targeted In Managing Inflammatory Skin Condimentioning
confidence: 99%